Reactive power control using STACOM in power system / Nor Hissham Nordin - Nordin, Nor Hissham (2008)
This project focuses in reactive power control in power system using Distribution Static Synchronous Compensator (D-STACOM). Reactive power compensation is very important in AC transmission. The project is to understand the reactive power compensation using D-STACOM 12-pulse configuration with Pulse Width Modulation (PWM) switching technique. This analysis includes reactive power condition under three phase balanced fault condition and application of three phase fault impedances. It can be shown that three phase balanced fault condition will decrease the reactive power in the system. D-STATCOM has an ability to absorb or injected the reactive power in the system. The designed was tested on IEEE 13 bus bar system using PSCAD/EMTDC software.